A qualitative analysis of choosing and experiencing the Infantry as an occupation - Loebel, Greg A., author; Dik, Bryan, advisor; Kraiger, Kurt, committee member; Doe, Sue, committee member (Colorado State University. Libraries, 2017)
The purpose of this study was to gain a better understanding of why men chose the Infantry as an occupation when enlisting in the U.S. military in the post-9/11 era, as well as the potential meaning they experienced through their service as infantrymen. Interviews were conducted with 11 undergraduate students who had served in either the U.S. Army or U.S. Marine Corps as infantrymen, and had enlisted with the specific goal to serve in an Infantry occupational specialty. All of the participants had served at least one combat deployment as infantrymen to either Afghanistan or Iraq. Consensual Qualitative Research (CQR) was used to guide the study. Prominent themes that emerged relative to enlistment decision-making included strong desires to fulfill roles of being highly skilled combatants and experience combat; viewing the Infantry as the best means to fulfill those desires; and desires to serve a greater good. Prominent themes related to meaning experienced through Infantry service included fulfillment of desired roles of being warriors; having experienced growth through hardship; a sense of accomplishment and pride through being skilled at Infantry warfare and having done important things; and the incredibly strong sense of brotherhood and camaraderie shared with other infantrymen they served with. Lastly, prominent themes regarding how their prior service may influence their current civilian career trajectories included having enhanced discipline, motivation, leadership, and sense of purpose; feeling distinctly different and separate from civilians; continued sense of service; and a desire for peace and normalcy in civilian life. Results from this study offered an interesting perspective on post-9/11 era military enlistment motivations connected to one particular class of occupational specialties. The participants did not offer any economic reasons for their enlistment motivations. That is, they did not choose the Infantry because of college benefits or job skills developed in their Infantry occupations that may transfer to civilian occupations. Rather, they appeared primarily motivated in their enlistment choices by desires to seek intense, dangerous training and combat experiences and fulfill particular warrior identity roles not available in civilian life, all through a sense of discipline and service.